Role of cumulative biological risk in mediating socioeconomic disparities in cognitive function in the elderly: a mediation analysis - Jimmy Akrivos (BMJ Open, 2020)
Objectives To evaluate whether allostatic load (AL), a measure of cumulative biological risk, fully or partially mediates observed socioeconomic status (SES) differences in cognitive function in the elderly.Design Cross-sectional mediation analysis.Setting Community-dwelling US elderly who participated in the National Health and Nutrition Examination Survey (NHANES).Participants The NHANES uses a complex, multistage, probability sampling design to select a nationally representative sample. Of the 4976 elderly (60 years or older) who were selected, 3234 agreed to participate in the household and medical exam interviews (65% response rate).Primary and secondary outcome measures Performance on the Digit Symbol Substitution Test (DSST)—a measure of cognitive function.Results Relative to participants with the lowest level of education or family income, participants who were college graduates (β=24.4, 95% CI 22 to 26.8, p<0.0001) or in the highest income quartile (β=17.3, 95% CI 15.2 to 19.4, p<0.0001) had the highest DSST scores and the least AL burden (β=−0.72, 95% CI −0.98 to −0.47 and β=−0.82, 95% CI −1 to −0.57; p<0.0001, respectively). Although, AL was significantly negatively associated with cognitive performance (β = −1, 95% CI −1.4 to −0.5, p<0.0001), it mediated at most 4.5% of the SES effect on DSST performance.Conclusions The findings suggest that AL, as measured by a summary index of parameters for cardiovascular function, metabolism and chronic inflammation, is not a significant mediator of SES-related differences in cognitive function in the elderly. Further efforts are required to elucidate the exact physiological pathways and mechanisms through which SES impacts cognitive function in late life.